2019
DOI: 10.12740/app/105489
|View full text |Cite
|
Sign up to set email alerts
|

Study of various factors affecting compliance in schizophrenia: A single center experience in India

Abstract: Aim of the study: Schizophrenia is a major psychiatric disorder, imparting a major burden in health care sector. Many treatments are available now a days to treat schizophrenia, although, its burden is not decreasing. The main reason behind this is noncompliance to treatment. This study aims to find out the noncompliance prevalence and to study influence of sociodemographic factors, treatment related variables, illness related variables and various subjective reasoning in patients with schizophrenia.Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Most studies did not find any association between age and MNA. [ 7 , 10 , 14 , 20 , 33 , 36 , 37 , 39 - 41 , 47 , 49 ] Younger-age group had better adherence in one study,[ 21 ] while a lower age was associated with poorer adherence in two studies. [ 24 , 35 ] Several studies did not find any association between gender and MNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies did not find any association between age and MNA. [ 7 , 10 , 14 , 20 , 33 , 36 , 37 , 39 - 41 , 47 , 49 ] Younger-age group had better adherence in one study,[ 21 ] while a lower age was associated with poorer adherence in two studies. [ 24 , 35 ] Several studies did not find any association between gender and MNA.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 , 35 ] Several studies did not find any association between gender and MNA. [ 10 , 15 , 17 , 20 , 21 , 24 , 36 - 38 , 40 , 41 , 46 , 47 ] Four studies found that compliance was better in females,[ 25 , 26 , 33 , 35 ] while one study found that female gender was associated with MNA. [ 7 ] Most studies did not find any association between education and MNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) describes medication nonadherence as "a case in which a person's behavior in taking medication does not correspond with agreed recommendations from health personnel" (Semahegn et al, 2020). In contrast, nonadherence was de ned as a failure to follow instructions and advice from service providers (Shah et al, 2019). Nonadherent patients are reported to be 70% more likely to be admitted to the hospital (Ljungdalh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) describes medication non-adherence as "a case in which a person's behaviour in taking medication does not correspond with agreed recommendations from health personnel (Semahegn et al, 2020). Contrastingly, non-adherence has been de ned as a failure to follow instructions and advice from service providers (Shah et al, 2019). Non-adherent patients are reported to be 70% more likely to be admitted to the hospital (Ljungdalh, 2017).. Non-adherence in mental diseases ranges from 70% to 80%, and in depression alone and bipolar disorder, it is between 26.5% and 70% (Alpak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%